Книга и проблемный метод изучения общественных наук в системе партийного образования - Тамошюнас, Леонас (Knygotyra, 1985)
The Communist party of the Soviet Union attaches a great importance to ideological work, calls for its ideological content and theoretical improvement, efficiency and for close ties with its practical activity in building socialism and communism. The development of a deep and firm Marxist-Leninist outlook is the basis of the whole ideological education. The problemic method in studying the Marxist-Leninist theory is the most important means favoring the propaganda efficiency. The role of the book and library under the problemic method in studying social sciences (which has not been studied yet) is covered in this article. The significance of the optimum choice of literature for various methodical and teaching problems is disclosed. The role of library in students’ independent work preparing for seminars, concluding sessions, theoretical conferences is discussed by the problemic method.The role of literature and technical equipment in some other forms of the teaching process is shown as well. The use of literature promotes the independence of students within the party education system, encourages their creative activity in solving problem issues. Numerous aspects of the optimum use of literature and technical equipment should be practically tested by teaching problem method. Nevertheless even the conclusions obtained can be used in education and propaganda.